PERAN GURU MENANAMKAN KARAKTER DISIPLIN ANAK USIA 5-6 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL KORPRI - jeli, Anjeli (Universitas Tanjungpura, 2023)
The research aims to describe the teacher's role in instilling the character of discipline in children aged 5-6 years at TK Aisyiyah Bustanul Athfal Korpri, Sungai Raya District. Researchers used a descriptive method with a qualitative approach. The research participants in this study were 2 Aisyiyah Bustanul Athfal Kindergarten teachers in Sungai Raya District. Data collection techniques that researchers use are observation, interviews and documentation. Researchers conducted data analysis by collecting data, reducing data, presenting data and drawing conclusions. The technique of checking the validity of the data is using triangulation and member checks. The results showed that the teacher's role in instilling the character of discipline in children aged 5-6 years at TK Aisyiyah Bustanul Athfal Korpri Sungai Raya District was to carry out their role as guides, role models and facilitators. The role of the teacher as a guide is to inform, direct, remind and supervise children through habituation of discipline. As an example, the teacher gives an example of discipline through habituation. As a facilitator, namely the teacher provides convenience and provides facilities through habituation at school.